'[...] the first handsome mathematical lady I've ever seen!' On the role of beauty in portrayals of Sofia Kovalevskaya. Issue 3 (2nd September 2017) - Kaufholz-Soldat, Eva
Abstract : For more than a century, the life of the Russian mathematician and author Sofia Kovalevskaya 1 (1850–91) has fascinated scholars and laymen alike. Among the many aspects discussed, her looks have aroused a significant interest. Hereby, a striking dichotomy becomes apparent, as she has been described both as rather unattractive or a ravishing beauty. Moreover, her beauty (or lack thereof) is often considered a pivotal issue in her vita and for her scientific career in particular. This article aims to present the scope of descriptions of Kovalevskaya's looks from the very first biographical accounts to her portrayal in modern literature, by highlighting some of the most influential examples in their historical context under special consideration of the changing views of the mathematician and women in science in general.